Photodynamic therapy with verteporfin is effective, but how big is its effect? Results of a systematic review. Issue 2 (21st January 2004) - Meads, C; Hyde, C
Abstract : Background: In 2001 the National Institute for Clinical Excellence (NICE) was asked to issue guidance for England and Wales on the use of photodynamic therapy (PDT). This process has been protracted, partly because of a dispute over the magnitude of beneficial effect. This article examines the origins of the debate about the true treatment effect size for PDT with verteporfin. Methods: A systematic review of the clinical effectiveness of PDT compared with current practice was undertaken. Searches in Medline, Embase, the Cochrane Library, and the Internet, updated to January 2003, revealed two fully published and four ongoing randomised controlled trials. Results: The results of the two published trials (TAP and VIP) consistently showed that overall, PDT with verteporfin is more effective than placebo in slowing the rate of vision loss. In the TAP trial, 12 or more subgroup analyses were undertaken on the primary outcome measure and in VIP, 10 subgroup analyses but only on a subset of the trial participants. Subgroup analysis results were found to be inconsistent between the two trials, with VIP suggesting that verteporfin was equally effective in occult as in mixed lesions and TAP suggesting that verteporfin was more effective in the predominantly classic subgroup. Discussion: For several reasons it was considered that the most likely estimate of the predominantly classic subgroup effect size was the whole trial result. This has implications for the relationship between cost and benefit, the subject of intense debate. Results of the ongoing trials should help to clarify this subgroup effect size issue.